Molecular Mechanisms for the Modulation of Selected Inflammatory Markers by Dietary Rice Bran Oil in Rats Fed Partially Hydrogenated Vegetable Fat. Issue 4 (3rd March 2016) - Rao, Y. Poorna Chandra; Kumar, P. Pavan; Lokesh, B. R.
Abstract: Industrially produced partially hydrogenated vegetable fat (PHVF) contains trans fatty acids (TFA) mostly comprising elaidic acid (EA, 18:1∆9t). Though, the harmful effects of TFA on health have been repeatedly publicized, the fat containing TFA have been continued to be used as a cooking medium in many regions of the world. The adverse effects of PHVF on oxidative stress and inflammatory markers and the possible ameliorative action of rice bran oil (RBO) on these markers were evaluated. Weaning rats were fed a AIN‐93 purified diet supplemented with the following lipids: groundnut oil (GNO, 10 wt%), PHVF (10 wt%), RBO (10 wt%), PHVF blended with RBO at 2.5, 5.0 and 7.5 wt% levels. The final concentration of the lipids in the diet was maintained at 10 wt%. Rats were fed these diets for 60 days. They were sacrificed and analyzed for oxidative stress and inflammatory markers. The rats fed PHVF showed lower levels of lipid peroxidation and hepatic antioxidant enzymes. The rats fed PHVF‐containing diets showed enhanced levels of interleukin‐1β, C‐reactive proteins and also showed enhanced levels of paw inflammation when injected with carrageenan as compared to rats given GNO, RBO or PHVF blended with incremental amounts of RBO. The macrophages from rats fed diet containing PHVF showed up‐regulation in the expressions of cytosolic phospholipase A2 (cPLA2 ), nuclear factor‐κB p65, toll like receptor (TLR)‐2, TLR‐4 and down‐regulation in the expressions of peroxisome proliferator activated receptor gamma (PPAR)γ, adiponectin receptor (AdipoR)‐1 and AdipoR‐2 when compared to rats fed diet containing GNO, RBO and PHVF blended with RBO. It was concluded that dietary PHVF enhance pro‐inflammatory markers which can be reduced by judiciously blending PHVF with RBO.